Management of Post-implant Inferior Alveolar Neuropathy, Utilizing Autologous Fibrin Glue, Concentrated Growth Factors and Enriched Bone Graft Matrix—A Case Report with 5 Years Follow-Up - Siva Prakash Dhanaraj; Sriganesh Anguswamy; Narmadha Dominic; Arun Sarfoji; Kayathri; Ashwini Sukanya (Indian Journal of Dental Research)
This case report explains meticulous management of 5 year old, inferior alveolar nerve neuropathy, following placement of dental implants in the mandible. The imperative situation was that ‘implants placed were not in contact with the nerve, but triggered neuralgic pain’. The objective of the treatment was to identify, and eliminate the causative factor, and to promote nerve regeneration, with pain relief. Treatment protocol and inferior alveolar nerve [IAN] sensory function evaluation were done following ‘Inferior Alveolar Nerve Injury during Dental Implant Placement Surgery Protocol’ [IANIDIS—Protocol]. Impregnation of autologous concentrated growth factors and enriched bone graft matrix [Sticky Bone™], at the surgical site, aided effective hard and soft tissue regeneration, restoring comfort to the patient.